2017
DOI: 10.1021/acsearthspacechem.7b00062
|View full text |Cite
|
Sign up to set email alerts
|

High Abundance of Fluorescent Biological Aerosol Particles in Winter in Beijing, China

Abstract: Primary biological aerosol particles (PBAP) such as pollen, fungal spores, bacteria, and viruses represent a major subset of particulate matter for both coarse and fine aerosols. Although PBAP affect climate and human health, there still remains a large uncertainty regarding their sources and characteristics, especially in urban atmospheres. Here we combined online fluorescent biological aerosol particle measurements and offline fluorescent and biomarker analysis in winter in Beijing, a city suffering from sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
27
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 96 publications
5
27
0
3
Order By: Relevance
“…In addition, FL B and FL C particles in fine mode still strongly correlated with the fine mode non‐FAPs (For FL C, 3σ: R 2 = 0.72–0.90; 6σ: R 2 = 0.69–0.90; 9σ: R 2 = 0.67–0.88), which indicates that they might have similar source with non‐FAPs. This is similar to the findings in winter in Beijing (Yue et al, ) and is also indicated by the moderate correlations with biomass burning tracers (Tables S8 and S9).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…In addition, FL B and FL C particles in fine mode still strongly correlated with the fine mode non‐FAPs (For FL C, 3σ: R 2 = 0.72–0.90; 6σ: R 2 = 0.69–0.90; 9σ: R 2 = 0.67–0.88), which indicates that they might have similar source with non‐FAPs. This is similar to the findings in winter in Beijing (Yue et al, ) and is also indicated by the moderate correlations with biomass burning tracers (Tables S8 and S9).…”
Section: Resultssupporting
confidence: 91%
“…This can be explained that as particle size increases, the increasing quantity of constituent biomolecules leads to fluorescence intensity exceeding the baseline of other spectral band. This change pattern has also been observed in the atmosphere in winter in Beijing (Yue et al, ) and in laboratory experiments with nonbiological interferences (Savage et al, ). Collectively, as to number concentration, the fluorescent bioaerosols resided mainly in the fine mode (<~3 μm), while for mass concentration, they were dominated by coarse (2.5–10 μm) and Lcoarse particles (>10 μm; Figure S6).…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations